Sudden Stops and Optimal Self-Insurance - Kim, Jun. (Washington, D.C. : International Monetary Fund, 2008)
This paper presents a simple model of optimal reserves that can be easily calibrated to compute optimal reserves as well as the implied probability of a sudden stop for given reserves. The model builds upon the global games framework of Morris and Shin to establish a unique relationship between the probability of a sudden stop and the level of reserves. The calibration results for 15 selected emerging market countries in Latin America, Asia and other regions over the sample period of 1993-2006 suggest that the risk of sudden stops may have declined to a low level in recent years in all countries in the sample. The results also suggest that Asia and Russia may have been significantly over insured since early 2000s with estimated excess reserves of USD 1 trillion in total at end-2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet